2008
DOI: 10.1128/aem.01400-07
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Ocean Distribution of Rhodobacterales Bacteria as Primary Surface Colonizers in Temperate Coastal Marine Waters

Abstract: Bacterial surface colonization is a universal adaptation strategy in aquatic environments. However, neither the identities of early colonizers nor the temporal changes in surface assemblages are well understood. To determine the identities of the most common bacterial primary colonizers and to assess the succession process, if any, of the bacterial assemblages during early stages of surface colonization in coastal water of the West Pacific Ocean, nonnutritive inert materials (glass, Plexiglas, and polyvinyl ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
284
1
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 356 publications
(300 citation statements)
references
References 61 publications
10
284
1
5
Order By: Relevance
“…This difference in diversity may not only be due to PCR primer coverage and specificity but also may result from some experimental details that might improve the quality of our experiment (Dang et al 2008c;Li et al 2010). Indeed, some of the sediment bacterial groups uniquely found in the current study were also detected in previous surface-colonizing bacterial community analyses in Qingdao coastal seawater (Dang et al 2008a(Dang et al , 2011. In the present study, the Power Soil DNA Extraction Kit was used, which has been demonstrated to be an efficient DNA extraction method for marine sediments.…”
Section: Bacterial Taxonomic Diversity In Jiaozhou Bay Sedimentsmentioning
confidence: 54%
See 1 more Smart Citation
“…This difference in diversity may not only be due to PCR primer coverage and specificity but also may result from some experimental details that might improve the quality of our experiment (Dang et al 2008c;Li et al 2010). Indeed, some of the sediment bacterial groups uniquely found in the current study were also detected in previous surface-colonizing bacterial community analyses in Qingdao coastal seawater (Dang et al 2008a(Dang et al , 2011. In the present study, the Power Soil DNA Extraction Kit was used, which has been demonstrated to be an efficient DNA extraction method for marine sediments.…”
Section: Bacterial Taxonomic Diversity In Jiaozhou Bay Sedimentsmentioning
confidence: 54%
“…Meanwhile, sporadic oil spilling from the commercial ports near the bay mouth, intensive maricultural practices at the north area, along with red tides all make the situation even worse (Wang et al 2008;Dang et al 2010b;Deng et al 2010). A wide spectrum of environmental conditions and accordingly a widely varying bacterial community structure have already drawn the JZB many research interests in recent years (Dang et al 2008a(Dang et al , b, 2009b(Dang et al , 2010b. To date, however, studies that describe the spatiotemporal variations of the bacterial communities in JZB sediments are still limited.…”
mentioning
confidence: 99%
“…Hence, it is not surprising that this group was already identified to be associated with copepods in recent studies (Grossart et al 2009;Tang et al 2009a, b;Møller 2007Møller et al 2007Peter and Sommaruga 2008). Rhodobacterales are known to be rapid and successful primary surface colonisers (Porsby et al 2008;Dang et al 2008;Jones et al 2007). The Rhodobacterales phylotypes found in this study clustered with sequences from surface-attached (biotic and abiotic surfaces), but also free-living bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…I that contributed to decomposition of the organic matter in the sediment. The marine Roseobacter clade members are primary colonizers of surfaces in marine environments (Dang and Lovell, 2000;Dang et al, 2008), and relate to degradation of a multitude of organic compounds, sulfur metabolism, production of antibacterial compounds and symbiotic relationships with diverse marine eukaryotes (Moran et al, 2003(Moran et al, , 2007Brinkhoff et al, 2008). The growth of the partial Roseobacter clade members might be promoted further by the gradient in the physicochemical properties of the burrow environment (Marinelli et al, 2002) and stimulatory effects of grazing by Capitella species and protozoa (Alongi, 1985;Plante and Shriver, 1998).…”
Section: Discussionmentioning
confidence: 99%